2019
DOI: 10.21733/ibadjournal.584664
|View full text |Cite
|
Sign up to set email alerts
|

Assure Öğretim Tasarımı Modeli İle Olasılık Kavrambının Öğretimine Yönelik Bir Öneri

Abstract: The issue of probability is one of the issues that both teachers and students have difficulty in handling. In order to cope with the difficulties in teaching and to make the subject more probable, it is considered appropriate to apply an instructional design model to the students. The aim of this study is to make students understand the situation on the basis of 5E learning model. It is thought that probability teaching will have a positive effect on students according to Assure teaching model. At the end of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
1
0
3
Order By: Relevance
“…The current research aims at determining the meanings attributed by the students and the music teachers to the technology-supported blended learning activities designed with the ASSURE instructional design model. In studies where the ASSURE design model and blended learning activities are used together (AlNajdi, 2018;Çetinkaya, 2017;Karaduman et al, 2019;Valverde-Berrocoso & Fernández-Sánchez, 2020), it is seen that technology-supported learning tools are used. For example, AlNajdi (2018) designed a blended learning environment based on the ASSURE model in order to teach the Arabic alphabet to primary school students in the USA in an effective and fun way and concluded that students' pronunciation and reading skills improved as a result of the application.…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…The current research aims at determining the meanings attributed by the students and the music teachers to the technology-supported blended learning activities designed with the ASSURE instructional design model. In studies where the ASSURE design model and blended learning activities are used together (AlNajdi, 2018;Çetinkaya, 2017;Karaduman et al, 2019;Valverde-Berrocoso & Fernández-Sánchez, 2020), it is seen that technology-supported learning tools are used. For example, AlNajdi (2018) designed a blended learning environment based on the ASSURE model in order to teach the Arabic alphabet to primary school students in the USA in an effective and fun way and concluded that students' pronunciation and reading skills improved as a result of the application.…”
Section: Purpose Of the Researchmentioning
confidence: 99%
“…Deney ve Kontrol grubuna uygulanan ön test ve son test bulgularına göre ASSURE ÖTM ile hazırlanan bir ders planın etkili olduğu sonucuna ulaşılmıştır. Bu araştırma kapsamında elde edilen bu sonuç da, yapılan diğer araştırmalarda (Baran, 2010;Eren, Aktürk, Demirer ve Şahin, 2010;Özdemir ve Uyangör, 2011;Göksu, Özcan, Çakır ve Göktaş, 2014;Karakış, 2014;Çetinkaya ve Taş, 2016;Karaduman, Memnun ve Çakır. 2019; Gündüzalp ve Yıldız 2020) olduğu gibi benzer bir şekilde ASSURE ÖTM'nin etkililiğini göstermektedir.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Literatürde ASSURE ÖTM'ni ve uygulamalarını içeren farklı çalışmalara (Baran, 2010;Eren, Aktürk, Demirer ve Şahin, 2010;Özdemir ve Uyangör, 2011;Göksu, Özcan, Çakır ve Göktaş, 2014;Karakış, 2014;Çetinkaya ve Taş, 2016;Karaduman, Sezgin Memnun ve Çakır. 2019;Gündüzalp ve Yıldız 2020) rastlanmıştır.…”
Section: Introductionunclassified
“…Çalışmaların önemli bir kısmı öğretim uygulamalarına dayanırken bazı çalışmalar ise modelin uygulanmasına yönelik bir yol haritası sunmaktadır. Ülkemizde yapılan çalışmalar incelendiğinde ASSURE öğretim tasarım modeline uygun şekilde tasarlanan ders ve materyallerin öğrencilerin öğrenmelerinde etkili olduğu (Aktaş, 2016;Aybey, 2020;Baran, 2010;Çetinkaya & Taş, 2015;Durak, 2009;Eren, Aktürk, Demirer & Şahin, 2010), öğrencilerin derse yönelik motivasyonlarını artırdığı görülmüştür ( Karaduman, Sezgin, Memnun & Çakır, 2019;Karakış, 2014;Kaya, 2021).…”
Section: Introductionunclassified